Oxygen uptake from aquatic macrophyte decomposition from Piraju Reservoir (Piraju, SP, Brazil) - Bianchini Jr.,I. (2011)
The kinetics of oxygen consumption related to mineralisation of 18 taxa of aquatic macrophytes (Cyperus sp, Azolla caroliniana, Echinodorus macrophyllus, Eichhornia azurea, Eichhornia crassipes, Eleocharis sp1, Eleocharis sp2, Hetereanthera multiflora, Hydrocotyle raniculoides, Ludwigia sp, Myriophyllum aquaticum, Nymphaea elegans, Oxycaryum cubense, Ricciocarpus natans, Rynchospora corymbosa, Salvinia auriculata, Typha domingensis and Utricularia foliosa) from the reservoir of Piraju Hydroelectric Power Plant (São Paulo state, Brazil) were described. For each species, two incubations were prepared with ca. 300.0 mg of plant (DW) and 1.0 L of reservoir water sample. The incubations were maintained in the dark and at 20 ºC. Periodically the dissolved oxygen (DO) concentrations were measured; the accumulated DO values were fitted to 1st order kinetic model and the results showed that: i) high oxygen consumption was observed for Ludwigia sp (533 mg g-1 DW), while the lowest was registered for Eleocharis sp1 (205 mg g-1 DW) mineralisation; ii) the higher deoxygenation rate constants were verified in the mineralisation of A. caroliniana (0.052 day-1), H. raniculoides (0.050 day-1) and U. foliosa (0.049 day-1). The oxygen consumption rate constants of Ludwigia sp and Eleocharis sp2 mineralisation (0.027 day-1) were the lowest. The half-time of oxygen consumption varied from 9 to 26 days. In the short term, the detritus of E. macrophyllus, H. raniculoides, Ludwigia sp, N. elegans and U. foliosa were the critical resources to the reservoir oxygen demand; while in the long term, A. caroliniana, H. multiflora and T. domingensis were the resources that can potentially contribute to the benthic oxygen demand of this reservoir.